PENGARUH JENIS PREKURSOR DAN METODE PRENETRALISASI PADA MORFOLOGI PERMUKAAN KERNEL TERSINTER ZIRKONIA - Sarjono; Rahmadi, Gagad; Mutiara, Etty; Mujinem; Haryadi, Dedi (Urania: Jurnal Ilmiah Daur Bahan Bakar Nuklir, 2024)
Research activities have been carried out on the effect of precursor types and preneutralization methods on the surface morphology of sintered zirconia kernels. Surface morphology with minimum roughness is desired in the development of TRISO coating system. Several batches of broth solution were prepared by several routes using different types of precursors and preneutralization methods. The types of precursors used were zirconium oxynitrate and zirconium nitrate pentahydrate and the preparation of sol was carried out by precipitation-redispersion and urea decomposition. The experimental stages included sol preparation, broth preparation, gel-casting process, aging-washing-drying process, de-watering process, heat treatment of calcination and sintering, and visual examination of surface morphology. Sphericity measurements were carried out on dry spherical gels to study the level of saturation of the sol and its ability to convert instantly upon reaction with NH3 gas in the gel-casting process. The results of SEM visual observations of the surface of the sintered zirconia kernel show that the lowest surface roughness was given by the kernel from zirconium nitrate pentahydrate precursor with urea decomposition pre-neutralization method, and the roughest surface was given by the kernel from zirconium oxynitrate precursor with pre-neutralization method of precipitation-redispersion.